Anoreksija nervoza s prikazom primera - Arzenšek, Pia (Obzornik zdravstvene nege, 2005)
The article presents the summary of the diploma work Anorexia nervosa with a case study. Anorexia nervosa (AN) is presented together with its causes, specific symptoms and complications and the fact that their understanding is of crucial importance for the choice of relevant mode of treatment. The article stresses the importance of the role of the nurse in hospital treatment of patients with anorexia nervosa, and presents the measure called involuntary hospitalization which can prevent vital threat in patients with this kind of eating disorder. The above elements are presented through the study of a patient with AN. The link between theory and practice enabled us to form certain preventive measures which can be used before onset and before relapse of anorexia nervosa and which can represent better prognosis and lower mortality of patients with AN. Key role in treatment belongs to the individual her/his own will, strenghts and motivation for change, together with psychophysical and social support from her/his environment.
Keywords: anoreksija; Anoreksija nervoza; Anorexia nervosa; Eating disorders; Hospitalizacija; Hospitalization; medicinske sestre; Motnje hranjenja; preventiva; therapy; zdravljenje